How to Boost Countries' Climate Ambitions: Turning Gains from Emissions Trading into Gains for Climate - Christoph Böhringer; Carsten Helm; Laura Schürer (Center for Economic Studies and ifo Institute (CESifo), 2023)
The Nationally Determined Contributions (NDCs) under the Paris Agreement fall short of the abatement needed to reach the 2°C target. Emissions trading could be a "costless" means to reduce the ambition gap if countries used their gains from trade for additional abatement. However, this requires cooperative behavior. We show that with emissions trading, countries' non-cooperative choices of emissions reduction contributions can lead to even more abatement, provided that these contributions may not be lower than initial NDCs. Intuitively, countries with high climate damages raise their contributions if they can meet them partly through abatement in countries with low abatement costs.
Keywords: H23; Q54; Q56; Q58; C72; 330; Paris Agreement; emissions trading; NDCs; game theory